Recent advances in protein modifications techniques for the targeting N‐terminal cysteine. Issue 3 (11th June 2021) - Asiimwe, Nicholas; Al Mazid, Mohammad Faysal; Murale, Dhiraj P.; Kim, Yun Kyung; Lee, Jun‐Seok
Abstract: N‐terminal modifications of proteins have garnered the attention of chemical biologists because of their critical roles in numerous cellular processes, including protein translocation, protein structural and metabolic stability, and the regulation of the half‐life of proteins by a process known as "N‐end rule pathway." In addition, other posttranslational modification processes also depend on the N‐terminal signal sequences. Chemical probes are powerful tools that can be used to investigate N‐terminal modifications, to gain structural and functional insights into protein modification, protein‐protein interactions, protein localization, and protein dynamics. Most modifications target cysteine and lysine residues because of their high nucleophilicity. However, due to multiple occurrences of these residues in a protein at a given time, regioselective labeling can be quite difficult to accomplish. N‐terminal cysteine presents itself as a unique practical option to overcome regioselectivity and site‐specificity challenges. This review provides an overview of N‐terminal cysteine labeling tools, including N‐terminal cysteine condensation with aldehydes, cyanobenzothiazoles, cyclopropenones, and trans‐thioesterification. The review also highlights the technical challenges of each of the techniques, which need to be addressed to broaden the scope of these approaches. Abstract :